Pelvic Trauma - Desai, Amita A. (J Pediatr Intensive Care, 2015)
The leading cause of death in the pediatric population is trauma, of which pelvic injuries make up a very small percentage. Trauma to the pelvis can result in multiple injuries to the bony pelvis, rectum, bladder, and or the urethra. Although mortality in the pediatric population is typically secondary to associated injuries, pelvic hemorrhage can be a life-threatening event. The management of patients with complex pelvic injuries requires a multidisciplinary approach in order to achieve the best possible outcomes.